Hidroginástica na reabilitação vestibular para idosos com queixas de tontura - Teixeira, Clarissa Stefani (2008)
The complaints about dizziness and corporal unbalance are very common symptoms in elderly people. In order to restore the functions of balance or make it nearest to the normal, having as objective to extinguish the symptomology found in these individuals, the vestibular rehabilitation is proposed. In this sense, many exercises are developed as therapy; however, physical exercises practiced in groups, in different environments, for example, in the water, were not found. Nowadays, therapies practiced in this environment have been developed, however they are done in a non-conventional and individualized way. Thus, this study was aimed to verify the influence of the practices in hydrogimnastics, done in the traditional way, over the corporal balance and complaints about dizziness in elderly people. For the balance assessment it was used a dynamic posturography developed by Castagno, in 1994 in this assessment, six conditions, named sensorial organization test, were done for each individual with repetitions of three times and duration of 20 seconds each one. The displacements were incorporated to the formula for the calculus of the oscillation. For the complaints about dizziness it was used the Dizziness Handicap Inventory. For the data analysis it was used the descriptive statistics. The normality of the data was verified through the Shapiro-Wilk test, which did not indicate normal distribution. For the comparison it was used the tests Kurskal-Wallis e Wilcoxon, with 5% of level of significance. The results indicate differences, in the conditions of the sensorial organization test either in the elderly with or without complaints about dizziness. Specifically the complaints about dizziness, in the end of the hydrogimnastic exercises, were reduced, either in the physical and emotional aspects, as in the functional ones. Thus, it is possible to conclude that the hydrogimnastics practiced in its traditional way, in a general view, was a good therapy for the complaints about dizziness and corporal balance of elderly individuals.